The Incidence of Myocardial Injury after Loading Doses of Clopidogrel versus Prasugrel in the Candidates for Percutaneous Coronary Intervention: A Randomized Controlled Trial. Issue 2 (June 2018) - Rahmani, Reza; Jiriaee, Laya; Jiriaee, Zahra; Shafiee, Akbar; Zand Parsa, Amir Farhang
Abstract : Introduction: Prevention of myocardial injury is an essential issue in percutaneous coronary intervention (PCI). We compared the incidence of myocardial injury after loading doses of clopidogrel versus prasugrel in the candidates for PCI. Methods: In this randomized-controlled clinical trial, we enrolled 88 stable angina patients, candidate for PCI. Patients received either prasugrel (60 mg orally) (n = 42) or clopidogrel (600 mg orally) (n = 46). Serum levels of creatine phosphokinase muscle-brain type, cardiac troponin I, and high sensitive C-reactive protein were measured at baseline and 6 and 12 hours postprocedural. Primary endpoint was periprocedural myocardial infarction (MI), defined as elevation of cTn values (>5 times) in patients with normal baseline values or a rise of cTn values >20% if the baseline values are elevated. Results: Based on the levels of cTnI 6 hours after PCI, 1 patient (2.4%) had MI in the prasugrel group, whereas 4 patients (8.7%) had MI in the clopidogrel group. After 12 hours, 4 patients (9.5%) had MI in the prasugrel group versus 5 patients (10.9%) in the clopidogrel arm. There was no significant difference between the groups regarding the changes in cardiac specific enzyme levels. However, serum levels of cTnI were significantly lower in patients with myocardial injury in the prasugrel arm ( P < 0.001). Conclusions: Prasugrel is an effective antiplatelet drug in preventing periprocedural MI.